2020
DOI: 10.3390/cancers12040868
|View full text |Cite
|
Sign up to set email alerts
|

TIE2 Induces Breast Cancer Cell Dormancy and Inhibits the Development of Osteolytic Bone Metastases

Abstract: Breast cancer (BCa) cells disseminating to the bone can remain dormant and resistant to treatments for many years until relapsing as bone metastases. The tyrosine kinase receptor TIE2 induces the dormancy of hematopoietic stem cells, and could also induce the dormancy of BCa cells. However, TIE2 is also a target for anti-angiogenic treatments in ongoing clinical trials, and its inhibition could then restart the proliferation of dormant BCa cells in bone. In this study, we used a combination of patient data, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…Before these studies, only ECs were thought to express the angiopoietin (1)(2)(3)(4) receptor Tie2 [25]. Nowadays, some cell types have been discovered to express Tie2: endothelial cells (ECs), TEMs, a subset of TAMs, pericyte precursors of mesenchymal origin, a subset of hematopoietic stem cells, and some cancer cell lines [26][27][28]. Two studies showed that Tie2 is expressed mainly by intermediate monocyte (CD14 + CD16 + ), whereas one study shows that Tie2 is also expressed in non-classical monocyte (CD14 dim CD16 + ).…”
Section: Origins Of Tamsmentioning
confidence: 99%
“…Before these studies, only ECs were thought to express the angiopoietin (1)(2)(3)(4) receptor Tie2 [25]. Nowadays, some cell types have been discovered to express Tie2: endothelial cells (ECs), TEMs, a subset of TAMs, pericyte precursors of mesenchymal origin, a subset of hematopoietic stem cells, and some cancer cell lines [26][27][28]. Two studies showed that Tie2 is expressed mainly by intermediate monocyte (CD14 + CD16 + ), whereas one study shows that Tie2 is also expressed in non-classical monocyte (CD14 dim CD16 + ).…”
Section: Origins Of Tamsmentioning
confidence: 99%
“…By promoting the expression and secretion of plasmin and MMP-2, these signaling pathways trigger the migration of endothelial cells and promote tumor angiogenesis, leading to tumor growth and metastasis [37,38]. In addition, TIE2 can participate in the regulation of the dormancy process of breast cancer cells, leading to increased resistance to chemotherapeutic drugs [39]. In the current study, we found that ADR can promote EMT in breast cancer cells in vitro and is accompanied by upregulation of the vascular endothelial marker CD31 in vivo, suggesting that the metastasis induced by ADR is related to tumor angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a recent study demonstrated that SIRT7 antagonizes TGF-β signaling and inhibits metastasis of breast cancer [ 81 ]. On the contrary, a more recent study revealed that SIRT7 promotes Adriamycin-induced metastasis in breast cancer by interacting with TIE2 [ 82 ], a tyrosine kinase receptor that induced the dormancy of breast cancer cells, resulting in increased resistance to chemotherapy [ 117 ]. Given the limited studies conducted to date and contradictory findings, more studies are required to provide insight into the modulation of other signaling proteins (including transcription factors) by SIRT7 causing either tumor-suppressing or tumor-promoting effects in breast cancer.…”
Section: Mechanistic Roles Of Sirtuins In Breast and Prostate Cancermentioning
confidence: 99%